9
$\begingroup$

I've tried with this differential equation $\displaystyle \frac{dy}{dx} = \frac{1+xy}{x(1-xy)}$ , put $u=xy$ then $\displaystyle\frac{du}{dx}=x\frac{dy}{dx}+y$ So,

It will be after editing $\displaystyle \frac{du}{dx} = \frac{1+u}{(1-u)} + \frac{u}{x}$

I am stuck here, keeping in mind only these three techniques are allowed: substitution, separating variable, and converting it to homogeneous equation

$\endgroup$
  • $\begingroup$ Are you sure of the ode. Maybe you are asked to solve $ \displaystyle \frac{dy}{dx} = \frac{y(1+xy)}{x(1-xy)} $. $\endgroup$ – Mhenni Benghorbal Sep 25 '13 at 7:10
  • $\begingroup$ @MhenniBenghorbal I've checked the textbook(it's in Arabic) many times, to be sure I've copy it correctly. the ODE that you mentioned is easily solvable , but I think there is a good chance to be a typing mistake. I'll ask my teacher. $\endgroup$ – SomeOne Sep 25 '13 at 11:20
  • $\begingroup$ Is this a first course in differential equations? $\endgroup$ – Mhenni Benghorbal Sep 26 '13 at 5:00
3
$\begingroup$

Approach $1$:

$\dfrac{dy}{dx}=\dfrac{1+xy}{x(1-xy)}$

$(x-x^2y)\dfrac{dy}{dx}=xy+1$

Let $u=\dfrac{1}{x}-y$ ,

Then $y=\dfrac{1}{x}-u$

$\dfrac{dy}{dx}=-\dfrac{1}{x^2}-\dfrac{du}{dx}$

$\therefore x^2u\left(-\dfrac{1}{x^2}-\dfrac{du}{dx}\right)=x\left(\dfrac{1}{x}-u\right)+1$

$-u-x^2u\dfrac{du}{dx}=2-xu$

$x^2u\dfrac{du}{dx}=(x-1)u-2$

$u\dfrac{du}{dx}=\dfrac{(x-1)u}{x^2}-\dfrac{2}{x^2}$

This belongs to an Abel equation of the second kind.

Let $v=\dfrac{1}{x}$ ,

Then $\dfrac{du}{dx}=\dfrac{du}{dv}\dfrac{dv}{dx}=-\dfrac{1}{x^2}\dfrac{du}{dv}$

$\therefore-\dfrac{u}{x^2}\dfrac{du}{dv}=\dfrac{(x-1)u}{x^2}-\dfrac{2}{x^2}$

$u\dfrac{du}{dv}=(1-x)u+2$

$u\dfrac{du}{dv}=\left(1-\dfrac{1}{v}\right)u+2$

Let $s=u-v$ ,

Then $\dfrac{ds}{dv}=\dfrac{du}{dv}-1$

$\therefore(s+v)\left(\dfrac{ds}{dv}+1\right)=\left(1-\dfrac{1}{v}\right)(s+v)+2$

$(s+v)\left(\dfrac{ds}{dv}+\dfrac{1}{v}\right)=2$

$(s+v)\dfrac{ds}{dv}+\dfrac{s}{v}+1=2$

$(s+v)\dfrac{ds}{dv}=1-\dfrac{s}{v}$

$(v-s)\dfrac{dv}{ds}=v(s+v)$

Approach $2$:

$\dfrac{dy}{dx}=\dfrac{1+xy}{x(1-xy)}$

$(yx+1)\dfrac{dx}{dy}=x-yx^2$

Let $u=x+\dfrac{1}{y}$ ,

Then $x=u-\dfrac{1}{y}$

$\dfrac{dx}{dy}=\dfrac{du}{dy}+\dfrac{1}{y^2}$

$\therefore yu\left(\dfrac{du}{dy}+\dfrac{1}{y^2}\right)=u-\dfrac{1}{y}-y\left(u-\dfrac{1}{y}\right)^2$

$yu\dfrac{du}{dy}+\dfrac{u}{y}=-yu^2+3u-\dfrac{2}{y}$

$yu\dfrac{du}{dy}=-yu^2+\dfrac{(3y-1)u}{y}-\dfrac{2}{y}$

$u\dfrac{du}{dy}=-u^2+\dfrac{(3y-1)u}{y^2}-\dfrac{2}{y^2}$

This belongs to an Abel equation of the second kind.

In fact all Abel equation of the second kind can be transformed into Abel equation of the first kind.

Let $u=\dfrac{1}{v}$ ,

Then $\dfrac{du}{dy}=-\dfrac{1}{v^2}\dfrac{dv}{dy}$

$\therefore-\dfrac{1}{v^3}\dfrac{dv}{dy}=-\dfrac{1}{v^2}+\dfrac{3y-1}{y^2v}-\dfrac{2}{y^2}$

$\dfrac{dv}{dy}=\dfrac{v^3}{y^2}-\dfrac{(3y-1)v^2}{y^2}+v$

Please follow the method in http://www.hindawi.com/journals/ijmms/2011/387429/#sec2

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.